2018
DOI: 10.1002/smll.201703982
|View full text |Cite
|
Sign up to set email alerts
|

Probing Adsorption Behaviors of BSA onto Chiral Surfaces of Nanoparticles

Abstract: Chiral properties of nanoscale materials are of importance as they dominate interactions with proteins in physiological environments; however, they have rarely been investigated. In this study, a systematic investigation is conducted for the adsorption behaviors of bovine serum albumin (BSA) onto the chiral surfaces of gold nanoparticles (AuNPs), involving multiple techniques and molecular dynamic (MD) simulation. The adsorption of BSA onto both L- and D-chiral surfaces of AuNPs shows discernible differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 70 publications
1
63
0
Order By: Relevance
“…Although these results revealed the effect of the protein shape, particle size, and surface properties on the corona formation, most simulations have been performed using a CG model or an implicit‐solvent model, which do not always accurately capture the dynamics and structural change of proteins and their interactions with particles. To overcome this, Shao and Hall, and Wang et al recently performed all‐atom simulations, showing the conformational change of SA protein adsorbed on gold nanoparticles. Tavakol et al's all‐atom and CG simulations showed the effects of glucose and cholesterol on the adsorption of plasma proteins onto PS particles .…”
Section: Introductionmentioning
confidence: 99%
“…Although these results revealed the effect of the protein shape, particle size, and surface properties on the corona formation, most simulations have been performed using a CG model or an implicit‐solvent model, which do not always accurately capture the dynamics and structural change of proteins and their interactions with particles. To overcome this, Shao and Hall, and Wang et al recently performed all‐atom simulations, showing the conformational change of SA protein adsorbed on gold nanoparticles. Tavakol et al's all‐atom and CG simulations showed the effects of glucose and cholesterol on the adsorption of plasma proteins onto PS particles .…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Adsorption separation based on porous materials has shown advantages due to their strong chiral recognition ability, longterm stability, and less complexity. 11 The exploration of chiral-functionalized porous materials as adsorbents for the highly efficient resolution of enantiomers has received extensive attention; these materials include metalorganic frameworks, 12,13 porous organic cages, 14,15 metalorganic cages 16,17 and composite porous materials. 18 However, the type of adsorbents for enantioselective adsorption was far more enough due to its challengeable preparation.…”
mentioning
confidence: 99%
“…This observation suggests that assembly of BSA at the PFD interface was looser than that at PFTBA. Figure d shows dynamic force microscopy (DFM) images that reveal homogeneous thicknesses of 2.78 ± 0.19 nm and 6.36 ± 0.12 nm for PFD and PFTBA, respectively, which agrees with the theoretical monolayer thickness of serum albumin protein whose diameter is 3–6 nm (albumin is the main component of serum protein) . Also, the low contrast of the images indicates a homogenous surface with root mean square (rms) roughness values within the picometer range (0.62 ± 0.11 nm for PFD and 0.49 ± 0.13 nm for PFTBA).…”
mentioning
confidence: 99%